Current molecular epidemiology and recombination of HIV type 1 subtypes in Northern Thailand - Praparattanapan J. (2014)
HIV subtype characterization is an important tool to monitor the genetic variation of the HIV epidemic. This study investigated the current HIV subtype distribution and recombination among the northern Thai population. An in-house genotypic assay of HIV protease and reverse transcriptase genes was performed on 420 plasma specimens from HIV-infected patients residing in several northern Thai provinces. HIV subtyping was determined by phylogenetic analysis. Three hundred and ninety-eight sequences (94.8%) were identified as CRF01-AE with the genetic distance of 1.848±0.957% and 12 (2.9%) as subtype B with the genetic distance of 4.186±0.849%. In addition, two sequences (0.5%) of HIV subtype C were found, suggesting that these patients were either immigrants from another country or were infected through heterosexual contact with HIV-infected subjects from another country. Bootscan analysis showed that there were eight (1.9%) unique recombinant forms (URFs) consisting of a recombinant of CRF01-AE with subtype B or subtype C. The information from this study is useful for prevention programs to halt the onward transmission of a particular HIV outbreak. However, characterization of the full genome of these CRF01-AE/B and CRF01-AE/C intersubtype recombinants, and also subtype C, is required for confirmation and elucidation. © 2011, Mary Ann Liebert, Inc.